Synthesis and Properties of 1-(2-(alkylamino)-2-oxoethyl) Pyridinium Chloride Surfactants. (April 2013) - Wang, Li-yan; Qin, Hong-lei; Wang, Lei; Huo, Shi-chao; Zhao, Bing; Song, Bo; Yan, Tie
A series of 1-(2-(alkylamino)-2-oxoethyl) pyridinium chloride surfactants was designed and synthesised by two steps. Four new compounds were obtained. The structures of all the synthesised compounds have been characterised by IR, 1 H NMR and elemental analyses. Surface activity and antibacterial activity of 1-(2-(alkylamino)-2-oxoethyl) pyridinium chloride surfactants were investigated. The critical micelle concentration and C20 values of the synthesised surfactants are low. The synthesised surfactants have good antibacterial activity for sulfate-reducing bacteria, metatrophic bacteria and iron bacteria in oil field injection water.